Financial supervision and policy coordination in the EMU - Karel Lannoo; Charles Wyplosz; Agnès Bénassy-Quéré (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
Contents: 1. Jürgen von Hagen, Jean Pisani-Ferry - Forum Economique Franco-Allemand /Deutsch-Französisches Wirtschaftspolitisches Forum ...1 – 2. Karel Lannoo - Financial Supervision in EMU ...3 – 3. Charles Wyplosz - Economic Policy Coordination in EMU: Strategies and Institutions...36 – 4. Agnès Bénassy-Quéré - Summary of the Proceedings of the Fourth Franco-German Forum ...61
Keywords: 330